2021
DOI: 10.1371/journal.pone.0245632
|View full text |Cite
|
Sign up to set email alerts
|

Pet owners’ and veterinarians’ perceptions of information exchange and clinical decision-making in companion animal practice

Abstract: One of the most complex aspects of the veterinarian-client-patient interaction is the clinical decision-making process. Research suggests that the approach to communication used by veterinarians can impact veterinary clients’ involvement in the decision-making process and their ultimate satisfaction. Using different approaches to the decision-making process may affect how information is exchanged and consequently how decisions are made. The objective of this study was to determine pet owners’ expectations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 35 publications
(95 reference statements)
6
83
0
4
Order By: Relevance
“…17 While outcome-based research in relation to SDM has been minimally explored in the veterinary field, findings from qualitative focus groups and semi-structured interviews with pet owners have highlighted the alignment between client communication expectations and SDM behaviours. 3,18,19 Clients have expressed a preference for partnership with their veterinarian, appreciation for tailored information and a desire to be fully informed about their options. 3,18,19 Nevertheless, measures of veterinarians' relationship-centred care scores indicate that dialogue within companion animal consultations primarily represent the veterinarian's agenda rather than the client's agenda.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 While outcome-based research in relation to SDM has been minimally explored in the veterinary field, findings from qualitative focus groups and semi-structured interviews with pet owners have highlighted the alignment between client communication expectations and SDM behaviours. 3,18,19 Clients have expressed a preference for partnership with their veterinarian, appreciation for tailored information and a desire to be fully informed about their options. 3,18,19 Nevertheless, measures of veterinarians' relationship-centred care scores indicate that dialogue within companion animal consultations primarily represent the veterinarian's agenda rather than the client's agenda.…”
Section: Introductionmentioning
confidence: 99%
“…3,18,19 Clients have expressed a preference for partnership with their veterinarian, appreciation for tailored information and a desire to be fully informed about their options. 3,18,19 Nevertheless, measures of veterinarians' relationship-centred care scores indicate that dialogue within companion animal consultations primarily represent the veterinarian's agenda rather than the client's agenda. 20 In contrast to human medicine, [15][16][17][21][22][23] there has been limited research into the use of SDM in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…In many societies, dogs are no longer treated as mere pets but more like family members whose well-being is a significant quality-of-life (QOL) factor for their owners. The depth of such relationships is reflected in veterinary questionnaires indicating that most owners provide better medical care and comply with health check visits more rigorously for their dogs than they do for themselves [ 22 ]. Another important aspect of the role of dogs in our society is their involvement in essential human services.…”
Section: Canine Model Of Mammalian Agingmentioning
confidence: 99%
“…Patient care is a key focus for the veterinary profession, but recent research has revealed that small animal veterinarians (from here on veterinarians) are increasingly challenged by trying to balance concerns for the patient, the client, and the veterinarian personally. Empirical studies indicate that strong emotional relationships between the client and the animal [1][2][3][4][5][6][7], the client's financial resources [8][9][10][11], the veterinarian's own economic interests and working background including level of specialization and/or practice type [1] as well as time available for consultation [12][13][14] all impact veterinarian's work life and can lead to potential ethical concerns and challenges in clinical decision making.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the development of specialized skills and the implementation of new techniques enables veterinarians to offer diagnostic and treatment options that are almost as advanced as those in human medicine [1]. In that context, Springer and colleagues [1] found that veterinarians' use of new technologies and other developments is linked to a desire for self-improvement, and is an important source of motivation in their daily work life: Veterinarians may increasingly feel a desire, or an obligation, to advance veterinary medicine in order to provide best and up-to-date patient care [1,[14][15][16]. Perhaps as a consequence of this, the role of health insurance for dogs and cats is becoming increasingly important as a means to reduce the potential impact of clients' financial limitations on treatment options [9,16,17].…”
Section: Introductionmentioning
confidence: 99%